Neurodevelopmental phenotypes associated with pathogenic variants in SLC6A1. Issue 6 (18th May 2021) - Kahen, Ashley; Kavus, Haluk; Geltzeiler, Alexa; Kentros, Catherine; Taylor, Cora; Brooks, Elizabeth; Green Snyder, LeeAnne; Chung, Wendy
Abstract : Background: SLC6A1 encodes GAT-1, a major gamma-aminobutyric acid (GABA) transporter in the brain. GAT-1 maintains neurotransmitter homeostasis by removing excess GABA from the synaptic cleft. Pathogenic variants in SLC6A1 disrupt the reuptake of GABA and are associated with a neurobehavioural phenotype. Methods: Medical history interviews, seizure surveys, Vineland Adaptive Behavior Scales Second Edition and other behavioural surveys were completed by primary care givers of 28 participants in Simons Searchlight. All participants underwent clinical whole exome sequencing or gene panel sequencing. Additional cases from the medical literature with comparable data were included. Results: We identified 28 individuals with largely de novo pathogenic/likely pathogenic variants including missense (15/21 or 71%) and truncating variants (6/21 or 29%). Missense variants were largely clustered around the sixth and seventh transmembrane domains, which functions as a GABA binding pocket. The phenotype of individuals with pathogenic variants in SLC6A1 includes hypotonia, intellectual disability/developmental delay, language disorder/speech delay, autism spectrum disorder, sleep issues and seizures. Conclusion: Pathogenic variants in SLC6A1 are associated with a clinical phenotype of developmental delay, behaviour problems and seizures. Understanding of the genotype–phenotype correlation within SLC6A1 may provide opportunities to develop new treatments for GABA-related conditions.